Impact of surveillance among patients with resected pancreatic cancer following adjuvant chemotherapy - Wong, Selina K. (J Gastrointest Oncol, 2021)
BACKGROUND: Pancreatic adenocarcinoma carries a high risk of recurrence even after surgery and adjuvant chemotherapy. Current guidelines do not endorse routine surveillance imaging due to lack of evidence supporting a survival benefit. With current first-line palliative chemotherapy options, it is unclear whether surveillance allows for early detection of asymptomatic disease and therefore an improved opportunity to offer chemotherapy to fit patients. We sought to describe patterns of surveillance of resected pancreatic cancer at British Columbia (BC) Cancer and determine whether utilization of computerized tomography (CT) scans affected likelihood of receiving palliative chemotherapy at the time of recurrence. METHODS: A retrospective review was completed to identify patients treated at BC Cancer centres between 2010–2016 who had undergone curative intent resection and received at least one cycle of adjuvant chemotherapy. Information was collected on baseline characteristics, imaging scans done between adjuvant chemotherapy and recurrence, and receipt of palliative chemotherapy. Two cohorts were defined based on number of scans done between completion of adjuvant chemotherapy and recurrence: those with only 1 scan were defined as “symptomatic” recurrences and patients who had undergone more than 1 scan were considered “surveillance” recurrences. RESULTS: In total, 142 patients were included of which 115 (81%) patients developed recurrence. There were 22 patients (19%) in the “symptomatic” cohort and 93 patients (81%) in the “surveillance” cohort. Median time to recurrence 274 days (9.1 months) in the symptomatic cohort compared to 471 days (15.7 months) in the surveillance group. Patients who underwent surveillance scans were more likely to receive palliative chemotherapy at the time of recurrence, though statistical significance was not reached: 51% in surveillance group versus 27% in symptomatic group [odds ratio (OR) 2.11, 95% confidence interval (CI): 0.75–6.58, P=0.17]. CONCLUSIONS: Despite the absence of surveillance recommendations, the majority of patients underwent surveillance imaging. We demonstrated a non-significant increase in the likelihood of receiving palliative chemotherapy among patients who underwent surveillance scans. With more efficacious palliative chemotherapy options available, studies to determine whether receipt of chemotherapy in asymptomatic recurrences translates into improved survival and/or quality of life are warranted.